Ick! : delightfully disgusting animal dinners, dwellings, and defenses - Stewart, Melissa (National Geographic kids., 2020)
Explains the unpleasant habits, foods, homes, and behaviors of forty-five animals. Includes color photographs, a glossary, and further resources.